Prospective Randomized Controlled Trial to Analyze the Effects of Intermittent Pneumatic Compression on Edema Following Autologous Femoropopliteal Bypass Surgery - te Slaa, Alexander; Dolmans, Dennis E. J. G. J.; Ho, Gwan H.; Mulder, Paul G. H.; van der Waal, Jan C. H.; de Groot, Hans G. W.; van der Laan, Lijckle (World journal of surgery, 2011)
Background Patients who undergo autologous femoropopliteal bypass surgery develop postoperative edema in the revascularized leg. The effects of intermittent pneumatic compression (IPC) to treat and to prevent postreconstructive edema were examined in this study. Methods In a prospective randomized trial, patients were assigned to one of two groups. All patients suffered from peripheral arterial disease, and all were subjected to autologous femoropopliteal bypass reconstruction. Patients in group 1 used a compression stocking (CS) above the knee exerting 18 mmHg (class I) on the leg postoperatively for 1 week (day and night). Patients in group 2 used IPC on the foot postoperatively at night for 1 week. The lower leg circumference was measured preoperatively and at five postoperative time points. A multivariate analysis was done using a mixed model analysis of variance. Results A total of 57 patients were analyzed (CS 28; IPC 29). Indications for operation were severe claudication (CS 13; IPC 13), rest pain (10/5), or tissue loss (7/11). Revascularization was performed with either a supragenicular (CS 13; IPC10) or an infragenicular (CS 15; IPC 19) autologous bypass. Leg circumference increased on day 1 (CS/IPC): 0.4%/2.7%, day 4 (2.1%/6.1%), day 7 (2.5%/7.9%), day 14 (4.7%/7.3%), and day 90 (1.0%/3.3%) from baseline (preoperative situation). On days 1, 4, and 7 there was a significant difference in leg circumference between the two treatment groups. Conclusions Edema following femoropopliteal bypass surgery occurs in all patients. For the prevention and treatment of that edema the use of a class I CS proved superior to treatment with IPC. The use of CS remains the recommended practice following femoropopliteal bypass surgery.